A demonstration of the use of a unified service model for urban infrastructure networks. Issue 4 (3rd May 2019) - Kielhauser, Clemens; Adey, Bryan T
Abstract : Planning interventions on urban infrastructure networks requires the consideration of costs of interventions and interruptions to the service provided by the infrastructure. It also requires taking into consideration how these costs and interruptions change due to the proximity of close networks. For example, it is less expensive to replace a gas pipe if the road is open, and, if a pipe is being replaced, there is a probability that the adjacent water pipe will be hit, resulting in a loss of service. Determining the optimal intervention programme for a single network is challenging as one has to consider all the objects within the network. Determining the optimal intervention programmes for multiple networks is even more challenging, particularly because the number of possible intervention programmes explodes. In this paper, the application of a unified model of the service provided by urban infrastructure networks to be used in the search for optimal intervention programmes on multiple networks simultaneously is presented. By using a single equation for all networks, the model enables an increase in the speed of calculation compared to traditional models, as a single equation can be used. The reductions in accuracy from more traditional models are discussed.